IMPLEMENTASI PERENCANAAN KAS SEBAGAI UPAYA UNTUK MENCIPTAKAN REALISASI ANGGARAN YANG PROPORSIONAL PADA KANTOR BADAN KEUANGAN DAN ASET DAERAH KABUPATEN KUTAI BARAT - Ida Rahmawati, Yeremia Bernat, Elfreda Aplonia Lau (EKONOMIA, 2018)
The purpose of this study was to determine and analyze the implementation of cash planning conducted by the Office of the Regional Finance and Asset Agency of West Kutai Regency and the realization of a proportional budget. The formulation of this research problem is "Is the implementation of cash planning implemented by the Office of Finance and Regional Assets of West Kutai Regency able to create a proportional budget realization in fiscal year 2015-2017 with the percentage deviation â‰¤ 5%?".The basis of this research theory used in this study is public sector accounting, especially regarding cash planning and proportional budget realization. The hypothesis of this research is the implementation of cash planning done at the Office of Finance and Asset Agency of West Kutai Regency able to create a proportional budget realization in fiscal year 2015-2017 with high accuracy value where percentage deviation percentage â‰¤ 5%.The analytical tool used is the calculation of the deviation value based on the Regulation of the Director General of Treasury Number PER-03 / PB / 2010 concerning Estimation of Withdrawal of Daily Funds of Article 13 paragraph 5 Work Unit. The results showed that the implementation of cash planning by the Office of Finance and Regional Assets of West Kutai Regency and the proportional budget realization, where in 2015 the high accuracy of deviation value of (0.29%) means that the hypothesis is accepted, 2016 accuracy medium deviation value (12.28%) which means the hypothesis is rejected and in 2017 the low accuracy of deviation value of ( 60.70%), which means the hypothesis is rejected